1998
DOI: 10.1111/j.1600-0447.1998.tb10127.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids: possible role in patho‐physiology and therapy of Gilles de la Tourette syndrome

Abstract: High densities of cannabinoid receptors were found in the basal ganglia and hippocampus, indicating a putative functional role of cannabinoids in movement and behaviour. Anecdotal reports suggested beneficial effects of marijuana in Tourette's syndrome (TS). We therefore interviewed 64 TS patients with regard to use of marijuana and its influence on TS symptomatology. Of 17 patients (27%) who reported prior use of marijuana, 14 subjects (82%) experienced a reduction or complete remission of motor and vocal tic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 21 publications
6
68
0
5
Order By: Relevance
“…In 1998 a survey of a larger population confirmed a reduction in tic or complete remission in 82 % of patients [27]. The same authors used Δ 9 -THC capsules of varying strengths in a single dose in 12 patients (class II study) and reported improvement in scores of the Tourette Syndrome Symptom List and obsessive-compulsive behavior scores, with a decreased number of complex motor tics observed by the examiner [28].…”
Section: Tourette Syndrome Ticsmentioning
confidence: 98%
“…In 1998 a survey of a larger population confirmed a reduction in tic or complete remission in 82 % of patients [27]. The same authors used Δ 9 -THC capsules of varying strengths in a single dose in 12 patients (class II study) and reported improvement in scores of the Tourette Syndrome Symptom List and obsessive-compulsive behavior scores, with a decreased number of complex motor tics observed by the examiner [28].…”
Section: Tourette Syndrome Ticsmentioning
confidence: 98%
“…Indeed, pre-clinical studies have shown that blockade of CB1 receptors may be beneficial in the management of dyskinesias resulting from prolonged dopaminebased therapies in Parkinson's disease (Maneuf et al, 1997;Brotchie, 1998). Furthermore, oral administration of D 9 -THC has been reported to alleviate tics and compulsive behaviors in patients affected by Tourette syndrome (Mü ller-Vahl et al, 1998.…”
Section: Cannabinoids and Psychomotor Disordersmentioning
confidence: 99%
“…Anecdotal reports (Sandyk and Awerbuch, 1988;Hemming and Yellowlees, 1993;Müller-Vahl et al, 1998 and two controlled studies (Müller-Vahl, 2001;Müller-Vahl et al, 2002) provide evidence that marijuana (Cannabis sativa) and delta-9-tetrahydrocannabinol (D 9 -THC), the major psychoactive ingredient of marijuana, respectively, are effective in the treatment of tics and behavioral problems in TS.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our data are in agreement with a pilot study in 12 TS patients demonstrating no detrimental effect on verbal and visual memory, sustained and divided attention, reaction time, intelligence, and vigilance after a single-dose treatment with up to 10 mg D 9 -THC . From anecdotal reports, it is even suggested that in TS patients smoked marijuana might improve attention (Müller-Vahl et al, 1998Sandyk and Awerbuch, 1988).…”
mentioning
confidence: 99%